The Effect Of Regional Original Revenue, General Allocation Funds, And Special Allocation Funds On Economic Growth In The North Sulawesi Province - Stanny Sicilia Rawung; Tiatira C Poluakan; Bobby Hamenda (Jambura Equilibrium Journal, 2023)
The authority received by local governments from the regional autonomy system in order to collect and distribute funds independently as well as decide on development interests. Regional autonomy seeks to equalize growth/development in accordance with regional interests in order to increase regional development based on the capabilities of each region.The purpose behind this study is to analyze the effects of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on economic growth in North Sulawesi Province. This study uses a collection of period series information for some time, 2002-2021 to be precise. Multiple linear regression analysis method was used in this research. The results of the research findings show that: 1) PAD has no substantial influence on economic growth in North Sulawesi Province; 2) DAU has a positive but insignificant impact on economic growth in North Sulawesi Province; 3) DAK has a negative effect on economic growth in North Sulawesi Province; 4) Meanwhile, simultaneously PAD, DAU and DAK have a positive and substantial effect on economic growth in North Sulawesi Province. In addition to the effort to increase the value of regional income indicators, improving the quality of human resources (HR) as managers of indicators in sustainable regional autonomy policies is one of the important efforts for the implementation of regional autonomy to support regional economic growth.